CONSTRUCTION OF RELIGIOUS MODERATION IN SEYYED HOSSEIN NASR'S PERENNIAL PHILOSOPHY PERSPECTIVE - Theguh Saumantri (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
In essence, religion is a form of human expression concerning spiritual experience and the relationship with the Divine. In this regard, religion can be a source of strength and inspiration for individuals and communities to live a meaningful life. However, in the context of rapid globalization and modernization, conflicts and tensions often arise between different religious groups. In the context of religious moderation, the idea of perennial philosophy is used to understand religious pluralism. This research aims to explicate the ideas of Seyyed Hossein Nasr's perennial philosophy towards the plural religious reality and to use his thoughts in building an understanding of religious moderation. This research uses a literature review method with a philosophical approach that aims to understand the thoughts or theories of a figure. The results of this study explain the importance of understanding universal religious values in building harmony in practicing religion and establishing inter-religious dialogues to reduce conflict and promote peace among different religious followers. Thus, the construction of religious moderation from the perspective of Seyyed Hossein Nasr's philosophy can bring peace and harmony to a society that is becoming increasingly pluralistic and complex. Nasr also emphasizes the importance of maintaining fundamental spiritual and moral values in religions as an effort to avoid fundamentalism and extremism.